(3GdLeY Hjf GdUMjMjf (B( (3UMjMji GdHNGQi heSde (B)s - (3GdLhRbj , eMeO Hf YHO Gddg Hf eMeO Hf RcQjG GdTjHGfj, CHh HcQ,J (B388 (3g` s ((3SeQbfOi s)
(3ChdgG (B:s
(3GdMeO ddg GdeTchQ YfO GdfYe HMb eG JWhd Hg egG cJGH GdUMjM ef GdGNHGQ s
(3BNQgG (B:s
(3bGd (B: (3CeG HYO aEf GdNeQ fRd JMQjegG jhe fRd , hgj ef NeSI ef GdYPH hGdJeQ hGdYSd hGdHQ hGdTYjQ hGdNeQ eG NGeQ GdYbd s
(3GdfSNI HgG MhGTs
(3Cedi GdeNWhW ai SeQbfO SfI (B579s
(3HBNQgG SeGY ddfGSN GdePchQ Ydi CHh YHO Gddg GdaQZGfi Gdeed ai SfI GdfSN hcJH GdaQZGfi HUMI GdSeGYs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs